Impact of Ki-67 and E-cadherin expression on lymphovascular invasion in upper urinary tract urothelial carcinoma - Stojnev Slavica; Krstić Miljan; Janković-Veličković Ljubinka; Ristić-Petrović Ana; Milojković Maja; Jovanović Ivan; Stokanović Dragana; Ugrenović Slađana (Vojnosanitetski Pregled)
Bacground/Aim. Upper urinary tract urothelial carcinoma (UUT-UC) constitutes 5% of malignant neoplasms arising from transitional epithelium, but is more invasive than bladder cancer. Lzmphovascular invasion (LVI) is associated with biologically aggressive carcinoma and with occult metastases. The aim of this study was to investigate the correlation between LVI and immunohistochemical expression of two frequently routinely applied immunohistochemical biomarkers, Ki-67 and E-cadherin, in UUT-UC. Methods. The specimens from 106 patients with UUT-UC who had undergone nephroureterectomy were analyzed for pathologic parameters and LVI, while Ki-67 and E-cadherin expression were assessed by immunohistochemistry. Results. Ki-67 was overexpressed in 38% of the cases, while 45% of tumors demonstrated aberrant E-cadherin staining. The presence of LVI was significantly associated with tumor stage, grade, non-papillary growth, nodular invasion pattern, high Ki-67 labeling index and altered E-cadherin expression. Analyzing logistic regression models, we have shown that tumor properties such as stage, grade, growth and invasion pattern (p < 0.001), as well as the expression of Ki-67 and E-cadherin (p < 0.001) significantly predicted the presence of LVI. In the first model, only solid tumor architecture (p < 0.05) and nodular invasion pattern (p < 0.05) were significant predictors of LVI. In the second model, Ki-67 expression was found to improve the prediction of LVI (p < 0.05). Conslusion. Our results suggest that Ki-67 overexpression is an independent predictor of LVI in UUTUC, indicating the progression of the disease. E-cadherin staining adds no valuable information to LVI probability assessment. This emphasizes the importance of Ki-67 staining of UUT-UC sections in routine pathological practice. Patients with Ki-67 overexpression, especially in solid tumors with nodular invasion, should be monitored more closely after surgery. [Projekat Ministarstva nauke Republike Srbije, br. 175092: Etiology, diagnosis, prevention and therapy of endemic nephropathy and associated tumors of the urothelium - the significance of genome and proteome study]